2022
DOI: 10.3390/foods11111559
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Amylase Trypsin Inhibitors Aggravate Intestinal Inflammation Associated with Celiac Disease Mediated by Gliadin in BALB/c Mice

Abstract: Celiac disease (CD) is an autoimmune intestinal disorder caused by the ingestion of gluten in people who carry the susceptible gene. In current celiac disease research, wheat gluten is often the main target of attention, neglecting the role played by non-gluten proteins. This study aimed to describe the effects of wheat amylase trypsin inhibitors (ATI, non-gluten proteins) and gliadin in BALB/c mice while exploring the further role of relevant adjuvants (cholera toxin, polyinosinic: polycytidylic acid and dext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Similar to prolamins, the clinical relevance of ATIs and nsLTPs is attributed to their resistance to proteolysis and acid or heat exposure. In vitro studies revealed that, in addition to the well-recognized immune reaction to prolamins, CD is also associated with a humoral immune response directed against serpins (serine protease inhibitors), purinins, ATIs, globulins, farinins and lectins, also known as wheat germ agglutinin ( 40 , 43 , 44 , 140 ). However, lectins are not heat stable and lose their adverse biological effects as a result of heat exposure, such as cooking or baking ( 140 ).…”
Section: Components Causing Adverse Reactionsmentioning
confidence: 99%
“…Similar to prolamins, the clinical relevance of ATIs and nsLTPs is attributed to their resistance to proteolysis and acid or heat exposure. In vitro studies revealed that, in addition to the well-recognized immune reaction to prolamins, CD is also associated with a humoral immune response directed against serpins (serine protease inhibitors), purinins, ATIs, globulins, farinins and lectins, also known as wheat germ agglutinin ( 40 , 43 , 44 , 140 ). However, lectins are not heat stable and lose their adverse biological effects as a result of heat exposure, such as cooking or baking ( 140 ).…”
Section: Components Causing Adverse Reactionsmentioning
confidence: 99%
“…Each eld of view was magni ed 20 times, and the images were quanti ed using ImageJ software (version 1.8.0). The average optical density (AOD) was used to calculate the areas of immunohistochemically positive cells [19].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, ATIs are the triggers of Bakers’ asthma, a wheat allergy, which affects up to 10% of flour workers ( Salcedo et al, 2011 ; Huebener et al, 2015 ). Recent, studies indicated that ATIs might even have the potential to cause celiac disease ( Huebener et al, 2015 ; Yu et al, 2022 ) or are recognized by gluten-detecting enzyme-linked immunosorbent assays ( Fraberger et al, 2020 ). Nevertheless, the role of ATIs in celiac disease is scarcely investigated so far and occurrence of them in gluten (isolates) ( Wieser and Scherf, 2018 ; Lexhaller et al, 2019 ) even increases the complexity of this question.…”
Section: Introductionmentioning
confidence: 99%